The Association of Weaning Outcome with Left Ventricular Diastolic Dysfunction in Critically Ill Patients - Bushra Zafar, Fakhir Raza Haidri, Nazia Arain, Hafiz Wahaj Fatmi, Ramesh Kumar, Suprinka Rahejra, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The aim of this study is to investigate the correlation between left ventricular diastolic dysfunction and successful weaning from mechanical ventilation in patients who are critically ill. Methods: An observational study was conducted at the ICU of the Sindh Institute of Urology and Transplantation (SIUT) in Karachi from April 2022 to December 2022. Essential baseline features including age, gender, duration of hospital stay, and ICU admission were documented using a predetermined proforma. Throughout the spontaneous breathing trial (SBT), hemodynamic evaluation was performed and recorded. Furthermore, respiratory and echocardiography parameters during the SBT trial as well as weaning results were documented. Results: The research involved 103 participants, with the majority being male. Among the 40 individuals who had diastolic dysfunction, there was a noteworthy occurrence of weaning failure in 29 patients (72.5%) which was found to have statistical significance (p=0.004). Additionally, a significant correlation between LV diastolic dysfunction and in-hospital mortality (p=0.003) was discovered. In addition, an extended duration of mechanical ventilation exceeding five days significantly corresponded with LV diastolic dysfunction (p=0.007). Conclusion: The results of our study provide additional proof to reinforce the importance of left ventricular diastolic dysfunction in predicting weaning failure from mechanical ventilation. This discovery can help medical professionals understand better how monitoring a patient's cardiac function during weaning is crucial, particularly with critically ill individuals. By recognizing the significance of LV diastolic dysfunction in this context, doctors and nurses can take proactive measures to monitor and treat any potential issues. Keywords: Weaning outcome, Left ventricular diastolic dysfunction, critically ill patients